Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Ukuran Perusahaan terhadap Nilai Perusahan pada PT Ciputra Development Tbk Periode 2014-2024 - Andini Setiawati; Rizka Wahyuni Amelia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the partial and simultaneous effects of Investment Decisions, Financing Decisions, and Company Size on Company Value at PT Ciputra Development Tbk for the period 2014-2024. Company value is proxied by Price to Book Value (PBV), investment decisions by Price Earning Ratio (PER), financing decisions by Debt to Equity Ratio (DER), and company size by SIZE. The method used in this study is descriptive quantitative. The population of this study is the financial statements of PT Ciputra Development Tbk for the period 2014-2024, and the sample used is the financial position report, income statement, and share price of PT Ciputra Development Tbk for the period 2014-2024. The analysis methods used are descriptive analysis, classical assumption testing, multiple linear analysis, t-test, f-test, and coefficient of determination test using SPSS version 26. The results of the study show that partially, PER and DER do not have a significant effect on PBV, while SIZE has a negative and significant effect on PBV. Simultaneously, PER, DER, and SIZE significantly affect PBV with a coefficient of determination of 94.7%, indicating that the regression model has excellent predictive power. The remaining 5.3% is influenced by other variables outside the scope of this study.